On the usability of digital sleep interventions in sports - Klier, K.; Seiler, K.; Wagner, M. (German Journal of Exercise and Sport Research, 2022)
High sleep quality is highly related to better health and peak performance. Nowadays, multiple applications and platforms are available to track activity, to monitor heart rate, or to evaluate sleep quality. While activity tracking and heart rate monitoring are widely used, little is known about the potentials of digital tools to optimize sleep quality. Especially among athletes, who often suffer from reduced sleep quality because of full schedules and high competition performance pressure, interventions to maximize performance by optimizing recovery and sleep quality seem to be promising. In the present paper, we give an overview on existing research focusing on the potentials of digital interventions to enhance sleep quality among athletes. In particular, mindfulness-based digital interventions seem to be promising as they evidently foster high sleep quality and related health and performance patterns. Further, athletes can time- and cost-effectively integrate them into their daily routines. Future research is needed to empirically test the usability of digital features and suitable interventions to optimize sleep.